Residues and bio-energy generation: A case study modelling value chain optimisation in Tasmania. (1st April 2020) - Woo, Heesung; Moroni, Martin; Park, Joowon; Taskhiri, Mohammad Sadegh; Turner, Paul
Abstract: Internationally biomass residues, primarily from forestry and agricultural production cycles, are increasingly being used to produce bio-energy. This case study presents modelling of the potential socio-economic impacts from a proposed co-generation bio-energy plant (under 50 MW) in the Valley Central Industrial Precinct (VCIP) in Northern Tasmania. The modelling uses data related to residue availability and bio-energy generation output to examine and evaluate potential impacts under a range of scenarios. Potential bio-energy residue feedstock is categorised into viable onsite and offsite sources and quantified in terms of their different bio-energy outputs for different sized bio-energy plants. To complete the evaluation of the potential socio-economic impact of the proposed plant, analysis is conducted using the JEDI (Jobs and Economic Development Impact model). The results of the modelling indicate that the location, quality and quantity of biomass residue feedstock and optimal socio-economic impacts are best aligned with the local supply chain by a bio-energy plant of (10 MW). Importantly, the modelling presented in this paper excludes consideration of forest harvest residues as a potential source of biomass residues due to the lack of certainty on the viability of commercial supply to the VCIP. In this context, it is anticipated that the underlying assumptions and approach used in this case study will be of value to other regions exploring the viability of bioenergy generation from biomass residues. Highlights: Socio economic impact analysis is conducted to investigate optimal size of prospect biomass facility. Feedstock availability is critical factor in the biomass energy industry. A combined heat and power plant is the best option for the dried biomass feedstock. Under 25 MW biomass plant is the best option for the local industry in the case study area.